Barnaby Rudge: A Tale of the Riots of 'Eighty - Dickens, Charles, 1812-1870 (Salt Lake City, UT : Project Gutenberg, 2006)
"Barnaby Rudge: A Tale of the Riots of 'Eighty" by Charles Dickens is a historical novel published in 1841. Set against the backdrop of London's violent Gordon Riots of 1780, the story weaves together forbidden romances, a decades-old murder mystery, and the simple-minded Barnaby Rudge with his pet raven. As anti-Catholic fervor ignites the city, families are torn apart and ordinary people are swept into mob violence. Churches burn, homes are destroyed, and innocent lives hang in the balance in this tale of social upheaval. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Barnaby_Rudge
Release date is 2006-04-27
Produced by Donald Lainson; David Widger
Keywords: Historical fiction; Gordon Riots, 1780 -- Fiction; London (England) -- History -- 18th century -- Fiction; Apprentices -- Fiction; Political fiction; Mystery fiction; Locksmiths -- Fiction